Formação em Libras: um estudo da preparação dos docentes de biologia e química atuantes na rede estadual de ensino do município de Itacoatiara-AM - Barbosa, Sidrac Sadoc Rosas (Brasil, 2024)
This research aimed to analyze the training of Biology and Chemistry teachers in the state education network of the Municipality of Itacoatiara-AM to find out if they were able to teach deaf students. To achieve this objective, the research examined the profile of teachers and their academic training, using a qualitative and exploratory and analytical nature, the data was collected through field research, through data collection, bibliographic review and We used a questionnaire with open and closed questions as a collection instrument. The questionnaire was carried out with all nineteen teachers working in the urban area of the municipality and the resultsshowed the weakness in these teachers' Libras training to work with deaf students.